2023
DOI: 10.3389/fendo.2023.1252389
|View full text |Cite
|
Sign up to set email alerts
|

Global research landscape and trends of papillary thyroid cancer therapy: a bibliometric analysis

Bo Song,
Zheyu Lin,
Chuyao Feng
et al.

Abstract: BackgroundPapillary thyroid cancer (PTC) is the most common endocrine malignancy worldwide. The treatment of PTC has attracted extensive attention and discussion from the public and scholars. However, no article has systematically assessed the related literature. Therefore, we conducted a bibliometric and knowledge map analysis to reveal the dynamic scientific developments in the PTC therapy field.MethodsWe retrieved publications related to PTC therapy from the Web of Scientific Core Collection (WoSCC) on May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The Deep convolutional neural network for the automated detection and diagnosis of seizure using EEG signals (41) We performed cluster analysis and cluster dependency analysis of cited literature using CiteSpace 6.2.R6 advanced visualization software. In bibliometric analysis, tracing the sources of reference clustering can indicate the research base and research hotspots in academic fields (49). As shown in Figure 7A, the thematic clustering map of the study area identified 14 clusters with significant modularity and silhouette scores (Q = 0.8452; S = 0.9062) (50).…”
Section: Highly Cited Reference Analysismentioning
confidence: 99%
“…The Deep convolutional neural network for the automated detection and diagnosis of seizure using EEG signals (41) We performed cluster analysis and cluster dependency analysis of cited literature using CiteSpace 6.2.R6 advanced visualization software. In bibliometric analysis, tracing the sources of reference clustering can indicate the research base and research hotspots in academic fields (49). As shown in Figure 7A, the thematic clustering map of the study area identified 14 clusters with significant modularity and silhouette scores (Q = 0.8452; S = 0.9062) (50).…”
Section: Highly Cited Reference Analysismentioning
confidence: 99%
“…The global ranking of thyroid cancer incidence places it at fifth position, a notable increase observed in numerous countries since the 1980s (1). This rise can be attributed to advancements in detection and diagnosis techniques, resulting in a significant upsurge in the detection rates of papillary thyroid carcinoma (PTC) (1). PTC is the predominant type of thyroid cancer, affecting approximately 80% of patients (2).…”
Section: Introductionmentioning
confidence: 99%
“…Besides extracting the aforementioned information, they facilitate visualization of the results, [14,15] intuitively reveal the scientific development of cutting-edge knowledge, and help researchers grasp the current research status and trends in the field. Several bibliometric analyses have been conducted on Graves’ Ophthalmopathy, autoimmune thyroiditis, Hashimoto’ s thyroiditis, and thyroid cancer [16–21] ; however, to date, no bibliometric analyses exist on GD. Therefore, we conducted a bibliometric and visual analysis of GD research published in the Web of Science Core Collection (WoSCC) database from 2003 to 2023.…”
Section: Introductionmentioning
confidence: 99%